The effects of popular diets on bone health in the past decade: a narrative review - Peng, Yue; Zhong, Zikang; Huang, Cheng; Wang, Weiguo (Frontiers in Endocrinology, 2024)
Bone health encompasses not only bone mineral density, but also bone architecture and mechanical properties that can impact bone strength. While specific dietary interventions have been proposed to treat various diseases such as obesity and diabetes, their effects on bone health remain unclear. The aim of this review is to examine literature published in the past decade, summarize the effects of currently popular diets on bone health, elucidate underlying mechanisms, and provide solutions to neutralize the side effects. The diets discussed in this review include ketogenic diet (KD), Mediterranean diet (MD), caloric restriction (CR), high-protein diet (HP), and intermittent fasting (IF). Although detrimental effects on bone health have been noticed in the KD and CR diets, however, it is still controversial, while the MD and HP diets have shown protective effects, and the effects of IF diets are still uncertain. The mechanism of these effects and the attenuation methods gain attention and were discussed in recent years: the KD diet interrupts energy balance and calcium metabolism, which reduces bone quality. Ginsenoside-Rb2, metformin, and simvastatin have been shown to attenuate bone loss during KD. The CR diet influences energy imbalance, glucocorticoid levels, and adipose tissue, causing bone loss. Adequate vitamin D and calcium supplementation and exercise training can attenuate these effects. The olive oil component of the MD may be an effective constituent that protects bone health. HP diets also have components protect bone health, but their mechanism requires further investigation. In IF, animal studies have shown detrimental effects on bone, while human studies have not. Therefore, the effects of diets on bone health vary accordingly.